2009
DOI: 10.1093/nar/gkp004
|View full text |Cite
|
Sign up to set email alerts
|

Generation of single-chain LAGLIDADG homing endonucleases from native homodimeric precursor proteins

Abstract: Homing endonucleases (HEs) cut long DNA target sites with high specificity to initiate and target the lateral transfer of mobile introns or inteins. This high site specificity of HEs makes them attractive reagents for gene targeting to promote DNA modification or repair. We have generated several hundred catalytically active, monomerized versions of the well-characterized homodimeric I-CreI and I-MsoI LAGLIDADG family homing endonuclease (LHE) proteins. Representative monomerized I-CreI and I-MsoI proteins (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 34 publications
3
53
0
Order By: Relevance
“…In turn, the observed conformational changes are likely a prerequisite for cleavage to proceed. This concept is in agreement with the published literature for these proteins: several previous studies have consistently demonstrated that their specificity of cleavage (which required both the formation of a tightly bound complex and then the precise ordering and arrangement of both active sites around the two scissile phosphates) is considerably higher than their specificity of binding (which is largely dependent only on the establishment of an initial series of contacts, often largely localized to one protein domain) [21,37,38]. …”
Section: Discussionsupporting
confidence: 91%
“…In turn, the observed conformational changes are likely a prerequisite for cleavage to proceed. This concept is in agreement with the published literature for these proteins: several previous studies have consistently demonstrated that their specificity of cleavage (which required both the formation of a tightly bound complex and then the precise ordering and arrangement of both active sites around the two scissile phosphates) is considerably higher than their specificity of binding (which is largely dependent only on the establishment of an initial series of contacts, often largely localized to one protein domain) [21,37,38]. …”
Section: Discussionsupporting
confidence: 91%
“…Because wild-type I-CreI is a natural homodimeric enzyme, both efforts rely upon the ‘monomerization’ of the I-CreI protein to create a single-chain reagent in which the two subunits of the enzyme are linked by a peptide tether and then expressed in cis as a monomeric scaffold [110-112]. Armed with this construct, redesign efforts can then be conducted on individual protein domains (targeting corresponding half-sites of the desired genomic target) with the resulting constructs combined into a single polypeptide which is further optimized for optimal in vivo performance.…”
Section: Reviewmentioning
confidence: 99%
“…Computational studies have given rise to not only speci fi city re-engineering (Ashworth et al 2006 ) , but have also addressed the dimerization issue via targeting protein-protein interactions of the subunits (Fajardo-Sanchez et al 2008 ) as well as through mimicking nature with single-chain constructs (Grizot et al 2009, Li et al 2009 ) . Exhaustive analysis of the I-AniI scaffold Thyme et al 2009 ) has led to better computational methods that can exploit binding energy for designs (Thyme et al 2009 ) .…”
Section: Computational Redesignmentioning
confidence: 99%